R/V NATSUSHIMA NT06-19 Leg2 Cruise Data - JAMSTEC (JAMSTEC, 2006)
[CRUISE DATA] This site includes a cruise dataset acquired in NT06-19 Leg2 on R/V NATSUSHIMA from 2006-09-17 to 2006-09-22.
Observation contents: Bathymetry, Expendable Bathythermograph
Keywords: Research cruise; R/V NATSUSHIMA; oceans